2021
DOI: 10.2147/ijgm.s313584
|View full text |Cite
|
Sign up to set email alerts
|

KRT7 Overexpression is Associated with Poor Prognosis and Immune Cell Infiltration in Patients with Pancreatic Adenocarcinoma

Abstract: Background: Pancreatic adenocarcinoma (PAAD) is a deadly tumor with a high recurrence rate and poor prognosis. Keratin 7 (KRT7) is a member of the keratin gene family that is involved in the regulation of cell growth, migration and apoptosis in many cancers. However, the role of KRT7 and its biological functions in PAAD remain unclear. We systemically analyzed the expression and clinical values of KRT7 in PAAD. Methods: The Gene Expression Profiling Interactive Analysis (GEPIA), Oncomine and Human Protein Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Another large cluster comprised cells with high expression of the carcinoembryonic antigen-related cell adhesion molecules CEACAM5 and CEACAM6 , which mediate cell adhesion and promote tumour invasion 38 , as well as MUCL3 , which has been shown to enhance PDAC cell proliferation, migration and invasion 39 ; this was labelled Classical_invasive . A smaller cluster defined by high expression of KRT7 , an intermediate filament protein known to be overexpressed in pancreatic cancer tissues compared to non-malignant pancreatic tissue 40 , was labelled Classical_adverse since a correlation of KRT7 overexpression with poorer overall survival of PDAC patients has been suggested 41 . Finally, the smallest cluster comprised cells highly expressing regenerating family member 4 ( REG4 ), which is thought to play a role in carcinoma development from intestinal-type intraductal papillary mucinous neoplasms (IPMNs) 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another large cluster comprised cells with high expression of the carcinoembryonic antigen-related cell adhesion molecules CEACAM5 and CEACAM6 , which mediate cell adhesion and promote tumour invasion 38 , as well as MUCL3 , which has been shown to enhance PDAC cell proliferation, migration and invasion 39 ; this was labelled Classical_invasive . A smaller cluster defined by high expression of KRT7 , an intermediate filament protein known to be overexpressed in pancreatic cancer tissues compared to non-malignant pancreatic tissue 40 , was labelled Classical_adverse since a correlation of KRT7 overexpression with poorer overall survival of PDAC patients has been suggested 41 . Finally, the smallest cluster comprised cells highly expressing regenerating family member 4 ( REG4 ), which is thought to play a role in carcinoma development from intestinal-type intraductal papillary mucinous neoplasms (IPMNs) 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, clusters 3, 8, 9, 11, 13, were enriched for ‘basal-like’ marker gene expression and were therefore summarised as ‘Basal-like’. Among the ‘classical’ clusters, clusters 0 and 4 shared enrichment for invasion related genes such as CEACAM5 and CEACAM6 and were summarised as Classical_invasive; clusters 2, 5, 6, 10, 12, 14, shared expression of secretion related genes such as TFF1, TFF2 and OLFM4 and were therefore summarised as Classical_secretory ; cluster 1 did not show secretory features but high expression of KRT7 , associated with poorer outcome in PDAC 41 , and was therefore labelled Classical_adverse; and the REG4-expressing cluster 7 was labelled Classical_REG4 . Cell clusters and gene expression are visualised on the same UMAP representation as in Figure 2A.…”
Section: Supplementary Figuresmentioning
confidence: 99%
“…Moreover, high levels of either WISP1 or CD73 were correlated with the density of immunosuppressive CD8+ T cells [ 34 , 35 , 38 ], thus leading to PC growth, metastasis, and disease progression [ 34 ]. Expression of KRT7 has been significantly associated with immune infiltration of tumor immune cells and immunomodulators in other carcinomas [ 39 ]. Thus, KRT7-positive benign epithelial cells surrounding prostate tumors may be also involved in functional interactions with immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Roles have been described for keratins other than KRT7 in the immune system and inflammation, DNA damage response and resistance to apoptosis, or apico-basal polarization [ 55 , 56 ]. Functional enrichment analyses and GSEA indicated that KRT7 might be involved in the regulation of the p53 pathway in pancreatic adenocarcinoma [ 39 ]. KRT7 was also positively correlated with keratin-8 (KRT8) expression in an intra-cellular gene-gene correlation, with KRT8 having been identified as a pan-cancer early biomarker in a multi-scale integrated analysis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…KRT7 is a member of the keratin gene family and is specifically expressed in the simple epithelia lining the cavities of the internal organs and in the gland ducts and blood vessels. KRT7 was reported as a predictive factor of various types of cancer, such as colorectal cancer ( 41) and renal clear cell carcinoma (42), but bad prognostic factor in esophageal squamous cell carcinoma (43) and pancreatic adenocarcinoma (44). KRT7 was also reported to promote epithelialmesenchymal transition (EMT) of ovarian cancer (45).…”
Section: Discussionmentioning
confidence: 99%